Impact Angle-Based Section Design and Optimization of the C Post in Order to Improve the Safety and Structural Performance of Guardrails - Ozcanan, Sedat; Ozcan, Ozgur (Turkish Chamber Civil Engineers, 2025)
This study focuses on enhancing the performance of the C post in H1 containment-level guardrail systems by optimizing its design to better withstand angular impacts, common in roadside safety applications. Since the post plays a crucial role in transferring impact loads to the ground, modifications were made by adjusting the angle of the post edge that aligns with the impact direction, while keeping the perpendicular side constant. Two key test angles from EN1317 standards were used: a 20-degree angle (TB11) to assess safety metrics like the Acceleration Severity Index (ASI) and theoretical Head Impact Velocity (THIV), and a 15-degree angle (TB42) to evaluate structural performance, including working width and exit angle. Finite element modelling in LS-DYNA, followed by model validation and calibration, showed that aligning the C post angle more closely with crash angles improved both safety and structural integrity, resulting in a transition of the C post design toward a Z post shape with enhanced rigidity and performance.
Keywords: Guardrail systems; post performance; EN1317; finite element analysis; LS-DYNA